THE EFFECTIVENESS OF HALT TRADING IN REDUCING MARKET TURMOIL: A STUDY EVENT ON COMPANIES GOING PUBLIC ON THE INDONESIA STOCK EXCHANGE - Vijaya, Diota Prameswari; Irwansyah, M. Rudi; Marverissa, Rindhi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
A trading halt is a temporary suspension of stock trading due to a sharp decline in market indices or the emergence of events that could potentially disrupt market stability. This study investigates the effectiveness of trading halts on the Indonesia Stock Exchange (IDX) in calming market turmoil by analyzing market reactions through abnormal returns and trading volume activity (TVA) using the event study method. The sample comprises companies listed in the LQ45 Index between February and April 2025. The event window is five days before and after the halt announcement. Findings show significant differences in abnormal returns, with higher values before the trading halt, suggesting the policy failed to restore investor confidence. No significant differences were found in TVA. These results suggest that the trading halt policy in the Indonesian context has not been effective and indicate the need for improved communication and transparency to support investor sentiment.